Fli-1, an Ets-Related Transcription Factor, Regulates Erythropoietin-Induced Erythroid Proliferation and Differentiation: Evidence for Direct Transcriptional Repression of the Rb Gene during Differentiation - Tamir, Ami (American Society for Microbiology, 1999)
Erythropoietin (Epo) is a major regulator of erythropoiesis that alters the survival, proliferation, and differentiation of erythroid progenitor cells. The mechanism by which these events are regulated has not yet been determined. Using HB60, a newly established erythroblastic cell line, we show here that Epo-induced terminal erythroid differentiation is associated with a transient downregulation in the expression of the Ets-related transcription factor Fli-1. Constitutive expression of Fli-1 in HB60 cells, similar to retroviral insertional activation of Fli-1 observed in Friend murine leukemia virus (F-MuLV)-induced erythroleukemia, blocks Epo-induced differentiation while promoting Epo-induced proliferation. These results suggest that Fli-1 modulates the response of erythroid cells to Epo. To understand the mechanism by which Fli-1 regulates erythropoiesis, we searched for downstream target genes whose expression is regulated by this transcription factor. Here we show that the retinoblastoma (Rb) gene, which was previously shown to be involved in the development of mature erythrocytes, contains a Fli-1 consensus binding site within its promoter. Fli-1 binds to this cryptic Ets consensus site within the Rb promoter and transcriptionally represses Rb expression. Both the expression level and the phosphorylation status of Rb are consistent with the response of HB60 cells to Epo-induced terminal differentiation. We suggest that the negative regulation of Rb by Fli-1 could be one of the critical determinants in erythroid progenitor cell differentiation that is specifically deregulated during F-MuLV-induced erythroleukemia.